Role of calnexin and calreticulin in protein homeostasis within the endoplasmic reticulum - Williams, David B. (Henry Stewart Talks, 2012)
Introduction to the endoplasmic reticulum, Protein folding and quality control within the endoplasmic reticulum, Asn-linked glycosylation and oligosaccharide processing, Calnexin and calreticulin, Structure and functions, The Calnexin cycle, Recognition of substrate polypeptide by calnexin and calreticulin, The dual binding model, Role of ERp57 in glycoprotein folding by calnexin and calreticulin, Peptidyl prolyl isomerases within the endoplasmic reticulum, ER-associated degradation, Overview, Recognition of misfolded glycoproteins, The Glyco code of the ER